Migração, assentamento e reforma agrária: história da colonização de Machadinho D'Oeste/RO (1970-1990) - Silva, Ulisses Cassiano Rodrigues da (2024)
This research seeks to understand the process of occupation of the non-indigenous population in the region that one day would be the State of Rondônia, emphasizing the period between 1970 and 1990. In the time before the mentioned period, when the military government assumed control of the government in 1964, there was a distribution of land through INCRA. Livestock and agriculture ended up being prominent in that period. Thus, the military outlined strategies to demobilize the social movements in the South and Northeast, which had great visibility and number and which demanded agrarian reform and thus disturbed the military in the post-1964 period. The solution found was to relocate the peasants, landless workers, in the Amazon region. In the then Federal Territory of Guaporé, the colonization program planned by the Federal Government was commanded by INCRA, which granted lots in the areas intended for the Integrated Colonization Projects (PIC). According to some studies and publications on the occupation process that occurred in the current State of Rondônia, the defended idea is that the process of official colonization would have contributed to a land configuration with a predominance of large properties/latifundium. However, the official data, acquired from INCRA, shows that Rondônia has had adopted a land distribution policy with a focus on properties classified as small properties, as well as having a considerable portion of its area appropriated by small properties. Thus, we present the INCRA data, which shows the context of the migration of small farmers to this region by virtue of the Settlement Project of Machadinho. With the advent of the occupied lands, there was also the battle for the opening of the lots and demographic growth, leading to the emergence of the city of Machadinho D'Oeste.